Dereplication of Natural Product Antifungals via Liquid Chromatography–Tandem Mass Spectrometry and Chemical Genomics - Nathaniel J. Brittin; David J. Aceti; Doug R. Braun; Josephine M. Anderson; Spencer S. Ericksen; Scott R. Rajski; Cameron R. Currie; David R. Andes; Tim S. Bugni (Molecules)
Recently expanded reports of multidrug-resistant fungal infections underscore the need to develop new and more efficient methods for antifungal drug discovery. A ubiquitous problem in natural product drug discovery campaigns is the rediscovery of known compounds or their relatives; accordingly, we have integrated Liquid Chromatography–Tandem Mass Spectrometry (LC-MS/MS) for structural dereplication and Yeast Chemical Genomics for bioprocess evaluation into a screening platform to identify such compounds early in the screening process. We identified 450 fractions inhibiting Candida albicans and the resistant strains of C. auris and C. glabrata among more than 40,000 natural product fractions. LC-MS/MS and chemical genomics were then used to identify those with known chemistry and mechanisms of action. The parallel deployment of these orthogonal methods improved the detection of unwanted compound classes over the methods applied individually.